Integration of Critical Thinking Skills in Science Learning Using Blended Learning System - Prafitasari, Ferrinda; Sukarno, Sukarno; Muzzazinah, Muzzazinah (Universitas Pendidikan Ganesha, 2021)
The COVID-19 pandemic has caused all fields to face a situation that challenging. critical thinking skills must still be integrated into science learning with the situation because it is one aspect of 21st-century learning. An alternative to reducing face-to-face activities is that schools carry out mixed-system learning. The purpose of this study was to evaluate the integration of critical thinking skills in science learning using a blended learning system in elementary schools given the limitations in learning during the covid-19 pandemic. This research is a case qualitative research with descriptive proportion with a sample of 19 elementary school fifth-grade students. Data collection techniques used are observation, documentation, questionnaires, and interviews. Triangulation of sources and techniques used to validate data. The results showed that critical thinking skills in elementary school science learning using a blended learning system are still relatively low with data (Mo<Md<Me), mean = 14.10, and the largest percentage distribution of 47.37%. The percentage of the majority of the questionnaires answered never with details on the aspects of formulating the problem52.63%, analyze arguments and solve problems 48.42%, evaluate 57.89%. In conclusion, the integration of critical thinking skills with blended learning systems in elementary schools in science learning still needs to be considered because there are still obstacles in its implementation. The results of this study have implications for finding solutions to improve critical thinking skills in science learning with blended learning system learning to be more effective. The recommendation in this study is that teachers are more creative in implementing blended learning system learning strategies for success critical thinking skills in learning science students can be achieved well.